The Impact Of Work Culture And Work Ethics On Performance Through Motivation As A Mediating Variable Among Territorial Command Soldiers At Kodim 0824 Jember - Dinarso, Rahmat Cahyo; Cahyono, Dwi; Sanosra, Abadi (Jurnal Ekonomi, 2024)
This study examines the impact of work culture, work ethics, and work motivation on the performance of soldiers and civil servants at Kodim 0824 Jember. Utilizing a quantitative approach, data was collected through Likert-scale questionnaires and analyzed using Partial Least Squares (PLS). The findings indicate that both work culture and work ethics significantly influence motivation and performance, both directly and indirectly. A strong work culture enhances motivation by fostering a sense of belonging, teamwork, and commitment, while robust work ethics, defined by integrity, responsibility, and professionalism, directly contribute to higher performance levels. These results suggest that developing a supportive work environment and maintaining high ethical standards are critical for optimizing human resources. Consequently, these factors are essential for achieving organizational objectives and promoting effective regional governance. This study underscores the importance of targeted interventions that strengthen cultural values and ethical behavior to enhance the overall performance of personnel at Kodim 0824 Jember.